The impact of environmental endocrine disrupting compounds on ovine fetal adrenal gland development and function - Bolton, R.L. (2015)
Humans and wildlife are constantly exposed to ubiquitous environmental chemicals which have the capability to disrupt the endocrine system. These endocrine disrupting compounds (EDCs) are found within everyday items including food cartons, baby-milk formula and can even be inhaled in dust particles. In utero exposure to EDCs has been found to disturb normal fetal hypothalamic, pituitary, gonadal and thyroid function in both genders. In contrast, despite increasing evidence of correlation between EDCs and metabolic diseases, chemical effects on the adrenal gland have received little attention. This study examined ovine fetal adrenal glands available from pregnant domestic sheep (Ovis aries) exposed to a real-life cocktail of EDCs found within human sewage sludge fertiliser (normal agricultural practice). Ewes were exposed for 80 day windows (0-80, 30-110, 60-140), or continually throughout gestation (0-140 days) and fetal adrenals subjected to immunohistochemistry for specific markers (CYP17A1 and AGTR1) or to real time PCR for the target genes (CYP11A1, CYP17A1, 3βHSD, MC2R, AGTR1 and ER1). Adrenal zone thickness stained for AGTR1 and CYP17A1 protein were significantly reduced (p=0.037 and p=0.031 respectively). AGTR1 and CYP17A1 gene expression exhibited a significant treatment by gender interaction (p=0.027 and p=0.032 respectively) in the females from the mid and late gestation treatment groups. ER1 gene expression was also significantly reduced in mid and late treatment goups compared with controls (p=0.042). These data illustrate that in utero exposure to EDCs within sewage sludge dysregulates the developing ovine fetal adrenal gland. It is hypothesised that this fetal adrenal dysregulation may contribute to the increasing incidence of human metabolic disease.